Burnout and job satisfaction of intensive care personnel and the relationship with personality and religious traits: An observational, multicenter, cross-sectional study. (August 2017) - Ntantana, Asimenia; Matamis, Dimitrios; Savvidou, Savvoula; Giannakou, Maria; Gouva, Mary; Nakos, George; Koulouras, Vasilios
Abstract: Objectives: To investigate if burnout in the Intensive Care Unit (ICU) is influenced by aspects of personality, religiosity and job satisfaction. Research methodology: Cross-sectional study, designed to assess burnout in the ICU and to investigate possible determinants. Three different questionnaires were used: the Malach Burnout Inventory, the Eysenck Personality Questionnaire and the Spiritual/Religious Attitudes Questionnaire. Predicting factors for high burnout were identified by multivariate logistic regression analysis. Setting/Participants: This national study was addressed to physicians and nurses working full-time in 18 Greek ICU departments from June to December 2015. Results: The participation rate was 67.9% (n = 149) and 65% (n = 320) for ICU physicians and nurses, respectively). High job satisfaction was recorded in both doctors (80.8%) and nurses (63.4%). Burnout was observed in 32.8% of the study participants, higher in nurses compared to doctors (p < 0.001). Multivariate analysis revealed that neuroticism was a positive and extraversion a negative predictor of exhaustion (OR 5.1, 95%CI 2.7–9.7, p < 0.001 and OR 0.49, 95%CI 0.28–0.87, p = 0.014, respectively). Moreover, three other factors were identified: Job satisfaction (OR 0.26, 95%CI 0.14–0.48, p < 0.001), satisfaction with current End-of-Life care (OR 0.41, 95%CI 0.23–0.76, p = 0.005) and isolation feelings after decisions to forego life sustaining treatments (OR 3.48, 95%CI 1.25–9.65, p = 0.017). Conclusions: Personality traits, job satisfaction and the way End-of-Life care is practiced influence burnout in the ICU.